Effect of thermomechanical post-processing on chain orientation and crystallinity of electrospun P(VDF-TrFE) nanofibers. (2nd June 2017) - Baniasadi, Mahmoud; Xu, Zhe; Moreno, Salvador; Daryadel, Soheil; Cai, Jizhe; Naraghi, Mohammad; Minary-Jolandan, Majid
Abstract: The electromechanical coupling behavior in piezoelectric polymers strongly depends on their morphology. The electromechanical coupling is defined as the conversion between electrical energy and mechanical energy in piezoelectric materials. Geometry (nanofibers, films, etc.) as well as fabrication methods, and post-processing affect crystallinity, orientation, and size of the crystallites, and alignment of the chains in semicrystalline structure of these polymers. This study reports on the effects of thermal annealing and stretching (drawing) as two post-processing treatments on mechanical and piezoelectric properties of P(VDF-TrFE) (poly[(vinylidenefluoride)- co -trifluoroethylene]) nanofibers produced by electrospinning process. Tensile test, X-ray diffraction and 2D WAXD, DSC, polarized FTIR, and piezoresponse force microscopy (PFM) were utilized to investigate the post-processing – morphology – property relationship in these nanofibers. The results show that annealing and stretching (drawing) improved elastic modulus and strength of the nanofibers by more than two times, while piezo response of single fiber increased by ∼1.7 times, which overall resulted in ∼5.5 times enhancement in electromechanical coupling factor. Comparison between two post-processing treatments revealed that annealing had more effect on improvement of thermomechanical coupling factor as compared to drawing. Graphical abstract: Highlights: Effect of annealing and stretching on properties of P(VDF-TrFE) nanofibers was investigated. These processes improved elastic modulus and strength of the nanofibers by more than two times. Piezo-response of single fiber increased by ∼1.7 times. Overall, ∼5.5 times enhancement in electromechanical coupling factor was observed.